Codex Sinaiticus Arabicus and its family a Bayesian approach - Turnbull, Robert (Leiden Boston Brill, 2025)
"Arabic versions of the New Testament have been overlooked for too long. The Sinai New Finds of 1975 unearthed Codex Sinaiticus Arabicus which preserves an Arabic translation of the Gospels differing markedly from the Majority Text. Here Robert Turnbull undertakes a wide-ranging study of this version, discovering many lectionary manuscripts with the same text. Several open-access datasets are made available. Bayesian phylogenetics and other computational techniques are used to draw insights into the transmission history of this version and its place in the wider New Testament textual tradition. This Arabic version will be indispensable in future textual scholarship on the Gospels"--
Literaturverzeichnis: Seite 363-381
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, Textual; Bayesian statistical decision theory